Successful Surgical Treatment of Idiopathic Chylothorax in a Cat - Carrasco, Lara Patrícia Santos; de Oliveira, Renato Leão Sá; Moreira, Clarissa Martins do Rio; Santos, Carla Regina Gomes Rodrigues; Jardim, Mariana Palha de Brito; de Farias, Luiza Freire; de Souza, Heloisa Justen Moreira (Acta Scientiae Veterinariae, 2018)
Background: Chylothorax in cats represents a challenge due to the possibility of involvement of multiple etiologies and the harmful consequences resulting of the presence of the chylous effusion in the thorax. The causes include neoplasms in the thoracic cavity, heart disease and thoracic injuries. It is imperative that clinical nutritional and therapeutic and / or surgical management be immediate and directed to the treatment of the cause. The objective of this work was to report a case of idiopathic chylothorax in a domestic cat solved through surgical intervention and dietary maintenance applied. Case: A 4-year-old male cat, fed with diet for the age range of adult cats, was attended at the Veterinary Hospital of the Federal Rural University of Rio de Janeiro (HV - UFRRJ), with clinical complaint of difficulty breathing, inappetence, prostration and weight loss. In the clinical examination was verified intense tachypnea, presence of heart murmur, normocorated mucosae, dehydration 7%. The animal was sedated to be submitted to radiographic examination of the thorax with pethidine and midazolam. Thoracic radiographs on the lateral, ventral-dorsal and orthostatic positions were realized and severe pleural effusion was observed in both hemitorax with drainage of 180 mL of lactescent fluid from the right hemithorax and 120 mL of left hemithorax liquid. Through analysis of cavity liquids the effusion was classified as chylous effusion. The hemogram showed a neutrophilic leukocytosis. Serum cholesterol and triglyceride concentrations (28 mg/dL and 43 mg/dL, respectively) were lower than the concentrations of the cavity liquid (67 mg/dL and 722 mg/dL, respectively). Ultrasound examination revealed no mass in the thoracic cavity and no changes in the pulmonary parenchyma. The echocardiographic examination was also performed and did not reveal any cardiac alterations. The initial treatment consisted of the clinical approach, through the exclusive alimentary management with low fat diet, in order to reduce to reduce the amount of chylous in the thorax. The rutine was administered at a dose of 250 mg/cat every 8 h orally. After 15 days, due to an unsatisfactory response to conservative treatment, surgical intervention was indicated. The technique used was pleural omentalization with block ligation of the thoracic duct without mesenteric lymphangiography together with pericardectomy and placement of the thoracic drain. During the postoperative period the animal remained under intensive care, with nasal oxygen therapy and intense analgesia during the first 72 h. After 20 days, the production of the chylous liquid was 2 mL/kg/ day, which made it possible to remove the drain. The cat received continuously with the exclusive diet of low fat to reduce the production of the chylous, without recurrence of chylous up to the present moment. Discussion: It is important to establish in a first approach of animals with chylous exudation the management of low-fat foods, along with appropriate pharmacological therapy, monitoring the patient in a constant and cautious way. If conservative clinical intervention is not satisfactory within 5 to 10 days, rapid surgical treatment is essential, due to the risk of fibrosing pleuritis with consequent involvement of the pulmonary parenchyma, as occurred in this report. Duct ligation surgery and the pericardectomy was satisfactory for the resolution of the constant chylous production in the thorax of the animal, as well as the use of the low fat diet was essential to reduce the chylous effusion and fibrosing pleurisy, both the interventions made possible the maintenance of the patient’s health and well-being. Keywords: feline, cavitary fluid, quilting effusion, thoracic duct.